Economic and management characterization of dehesa farms: implications for their sustainability (Agroforestry Systems, 2007)
Dehesa agroforestry systems occupy around 6 million ha in the Iberian Peninsula. Their economic and environmental sustainability depends on the maintenance of the extensive livestock farms which created this typical ecosystem. This work analyzes dehesa farms in the Extremadura region (SW Spain) using technical and economic indicators of 69 randomly selected holdings. Principal component analysis (PCA) allowed us to establish a valid model explaining 65.8% of the variance. The two principal components having most weight were Iberian pig production (explaining 20% of the variance of the model), and which ruminant species were raised on the farm (15% of the variance). A cluster analysis distinguished ﬁve types of farms: sheep farms at high and low stocking rates, beef cattle farms, wooded farms with mixed livestock, and farms with a high level of cropping activity. The most proﬁtable farms were those with either high overall livestock density or a high level of Iberian pig production. While high stocking density has historically attracted high levels of subsidy, production of Iberian pigs was proﬁtable because of the high value of the product. In the light of CAP reform, Iberian pig production seems the most readily sustainable type of farming for the dehesa system.

ANÁLISIS ECONÓMICO DE LAS EXPLOTACIONES EXTREMEÑAS DE DEHESA A TRAVÉS DE INDICADORES DE CAPITAL , COSTES , (Gestión Ambiental y Económica del Ecosistema Montado/Dehesa en la Península Ibérica, 2006)
En este trabajo se estudia la estructura técnico-económica de las explotaciones ganaderas de la dehesa extremeña, a través de indicadores técnicos y económicos. Se utiliza una metodología inspirada en la adaptación a nivel microeconómico del Sistema Europeo de Cuentas Económicas Integradas, aplicada a las cuentas económicas de la Agricultura y la Selvicultura. Los datos han sido obtenidos mediante la realización de encuestas a 76 titulares de explotaciones de dehesas de la Comunidad Autónoma de Extremadura realizadas durante los años 2004 y 2005. Las explotaciones estudiadas han sido fi ncas colaboradoras del proyecto “Desarrollo de un sistema de información para la gestión ambiental y eco- nómica del ecosistema dehesa/Montado en Extremadura y Alentejo”, fi nanciado por el INTERREG-III (SP4.E13).

Niveles de cargas ganaderas en la dehesa extremeña (Archivos de zootecnia, 2002)
This work analyzes the data collected from 143 sheep and/or cattle farms, representatives of the Extremaduran dehesa (semiarid grazing areas of the SW of Spain). A random survey was carried out in 2000, with an error of less than 5 percent and a confidence level of 95 percent. The aim of the survey was the evaluation of the stocking rate levels of these farms in 1999 and their evolution from 1993, first year after the CAP Reform of 1992. The effects of farm size for different stocking rates are studied. Significant differences were observed (p<0,05 and p<0,01) between the bigger and the lesser farm sizes. This shows a higher productive intensification when the grazing surface decreases. It is to mention a high correlation between the cattle units in sheep farms (UGMo) and the cattle units in the whole sample (UGMt) (r=0,867; p<0,01), as well as the association between sheep density and pig density variables (r=0,773; p<0,01). On the other hand, we can observe an inverse correlation between the levels of livestock density and the farm size, which is more significant in cattle farms.

Tipología de sistemas adehesados* (Archivos de Zootecnia, 2001)
This work analyzes a a group of livestock farms in semiarid grazing areas in Spain. The surface sample studied adds up to 80.000 hectares. The results are expressed according to the livestock prevalence of the farms. INTRODUCCIÓN